Bone lesions of Langerhans cell histiocytosis triggered by trauma in children. Issue 1 (30th June 2022) - Morimoto, Akira; Shioda, Yoko; Sakamoto, Kenichi; Imamura, Toshihiko; Imashuku, Shinsaku; ,
Abstract: Background: Bone lesions of Langerhans cell histiocytosis (LCH) may be triggered by trauma. Methods: The characteristics of pediatric patients in the JLSG‐02 study cohort who developed a bone lesion at the trauma site at diagnosis of LCH were analyzed retrospectively. Results: Of the 261 pediatric patients with LCH, 12 (4.6%), of median age 4.9 years, had trauma‐triggered bone LCH lesions at diagnosis, making them significantly older than the remaining patients ( P = 0.006). Trauma sites included the craniofacial regions in 10 patients and the lumbar spine and pelvis in one patient each. At the time of trauma, six patients had a bump at the site, whereas none had extradural hematomas or bone fractures. The median time from trauma to onset was 4 weeks. Of these 12 patients, three had isolated bone (IB) disease; four had multifocal bone (MFB) disease, including the bone lesion at the trauma site; and five had multisystem disease, including four with lesions in neighboring tissue and one with polyuria (posterior pituitary lesion) more than 1 year before the trauma‐triggered bone lesion. Treatment responses were good in all 12 patients and none died, but relapses were observed in two patients, one each with IB and MFB disease. Conclusions: About 5% of pediatric patients with LCH developed new trauma‐triggered bone lesions at a relatively old age. These lesions can manifest as IB, or, in patients with underlying LCH diseases, as MFB or multisystem. Good clinical outcomes were observed in these patients.